Piloting a New Approach to the Treatment of Obesity Using Dexamphetamine - Poulton, Alison S.; Hibbert, Emily J.; Champion, Bernard L.; Cook, Traci L.; Alais, David; Coulshed, David S. (Frontiers in Endocrinology, 2015)
Background and aims There is a clear need for a new approach to the treatment of obesity which is inexpensive and is effective for establishing lifestyle change. We conducted a pilot study to evaluate whether dexamphetamine can be used safely, combined with diet and exercise, for treating obesity. Our ultimate aim is to develop a 6 month treatment program for establishing the lifestyle changes necessary for weight control, utilising dexamphetamine for its psychotropic effect on motivation. We viewed the anorexigenic effect as an additional advantage for promoting initial weight loss. Methods Obese adults were treated with dexamphetamine for 6 months (maximum of 30mg twice daily), diet and exercise. Weight, electrocardiogram, echocardiogram and blood pressure were monitored. Results Twelve out of 14 completed 6 months treatment. Weight loss by intention to treat was 10.6kg (95%CI 5.8-15.5, p<0.001). The mean weight gain in the 6 months after ceasing dexamphetamine was 4.5kg (95%CI 1.9 to 7.2, p=0.003), leaving a mean weight loss at 12 months from baseline of 7.0kg (95%CI -13.4 to -0.6, p=0.03). All reported favourable increases in energy and alertness. Dose-limiting symptoms were mood changes (2) and insomnia (2). None had drug craving on ceasing dexamphetamine and there were no cardiac complications. Among the 7 women, there was a significant correlation for those who lost most weight on treatment to have the least regain in the following 6 months (r=0.88, p=0.009). Conclusions Our treatment with dexamphetamine, diet and exercise was well tolerated and effective for initial weight loss. Future research will focus on identifying baseline predictive variables associated with long-term weight control. Trial registration: ACTRN12612000831886